2020
DOI: 10.1007/s00198-020-05639-y
|View full text |Cite
|
Sign up to set email alerts
|

Early clinical effects, safety, and appropriate selection of bone markers in romosozumab treatment for osteoporosis patients: a 6-month study

Abstract: Our 6-month study showed the usefulness of romosozumab for preventing fractures and its safety. It was effective in patients with low baseline spine BMD, high TRACP-5b, and high iP1NP. Percent change from baseline of TRACP-5b and iP1NP after 1 month correlated with that from baseline of BMD after four to 6-month treatment. Introduction Romosozumab appeared as a new osteoporosis medication in Japan in 2019. It is an anti-sclerostin antibody which increases bone formation and suppresses bone resorption. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Besides, there were a few reports about the treatment of osteoporosis by romosozumab by comparing prior treatment of osteoporosis [ 5 , 6 ]; our study indicated that switch therapy after romosozumab was similar to the primary treatment of romosozumab. In regard to this point, Tominaga also suggested that the change of increase in BMD were naïve>teriparatide> bisphosphonate>denosumab in 6 months [ 6 ]. Moreover, Ebina also suggested that naïve, teriparatide, bisphosphonates and denosumab had higher increase of BMD in turn [ 5 ].…”
Section: Discussionmentioning
confidence: 57%
“…Besides, there were a few reports about the treatment of osteoporosis by romosozumab by comparing prior treatment of osteoporosis [ 5 , 6 ]; our study indicated that switch therapy after romosozumab was similar to the primary treatment of romosozumab. In regard to this point, Tominaga also suggested that the change of increase in BMD were naïve>teriparatide> bisphosphonate>denosumab in 6 months [ 6 ]. Moreover, Ebina also suggested that naïve, teriparatide, bisphosphonates and denosumab had higher increase of BMD in turn [ 5 ].…”
Section: Discussionmentioning
confidence: 57%
“…Amylin can repress the activity of osteoclasts, decline the bone absorption of basal and parathyroid hormone, stimulate the generation of cAMP via combining with the calcitonin receptor on osteoclasts, and constrain the mutual fusion of osteoclast precursor cells for the formation of mature multinuclear giant cells. Therefore, osteocyte is suppressed to influence bone metabolism [19] . Our study showed APN of 5.15 μg/mL or less and amylin of 15.38 pmol/L or less in patients were risk factors impacting the aggravation of pathological condition of POP, elaborating that the declined serum APN and amylin in patients might aggravate the severity of the pathological condition of POP.…”
Section: Discussionmentioning
confidence: 99%
“…3 Recently, some targeted drugs for osteoporosis have been approved for clinical use and exhibit excellent curative effects. [4][5][6] As a predominant source of osteoblasts, it is crucial to maintain osteogenic differentiation and proliferation of bone marrow mesenchymal stem cells (BMMSCs) to preserve bone homeostasis. 7 Furthermore, several studies have revealed that BMMSC-mediated osteogenic differentiation and proliferation can be downregulated or impaired by multiple factors in the bone marrow (BM), which is markedly associated with osteoporosis.…”
Section: Introductionmentioning
confidence: 99%
“…Current strategies for osteoporotic prevention and treatment focus on promoting bone regeneration, suppressing bone resorption, or a combination of both 3 . Recently, some targeted drugs for osteoporosis have been approved for clinical use and exhibit excellent curative effects 4–6 …”
Section: Introductionmentioning
confidence: 99%